2018
DOI: 10.1097/md.0000000000012042
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between esophageal pH-metry and esophagitis in gastroesophageal reflux disease in children

Abstract: Gastroesophageal reflux (GER) is the intermittent or permanent passage of stomach content into the esophagus and gastroesophageal reflux disease (GERD) is the reflux which triggers a whole set of symptoms or complications. The study compares the 24-hours esophageal pH-metry, used for diagnosis of the GERD, with the esophagitis degree observed at the upper digestive endoscopy.72 children were included, aged over 4 years old, admitted in a pediatric gastroenterology regional center in Northeast Romania, diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Gastroesophageal reflux disease (GERD) might result in the dilatation of intercellular space, an important histologic biomarker for erosive esophagitis in children 24 . Lupu et al 25 demonstrated a parallel relation between the scores of pHmetry and the endoscopic lesion. Thus, EGD is reserved for cases of GERD that are unresponsive to clinical treatment.…”
Section: Discussionmentioning
confidence: 94%
“…Gastroesophageal reflux disease (GERD) might result in the dilatation of intercellular space, an important histologic biomarker for erosive esophagitis in children 24 . Lupu et al 25 demonstrated a parallel relation between the scores of pHmetry and the endoscopic lesion. Thus, EGD is reserved for cases of GERD that are unresponsive to clinical treatment.…”
Section: Discussionmentioning
confidence: 94%
“…The pH-metry is based on the idea that the progression of the acid gastric content in the esophagus during reflux causes a decrease in intraesophageal pH. The method involves measuring the pH in the lower part of the esophagus for a certain period (in our study 24 h) by using an electrode located 5 cm above the cardia and attached to a portable pH-meter with batteries [10][11][12][13][14].…”
Section: Methodsmentioning
confidence: 99%
“…The electrode is lubricated first, then inserted nasally up to 5 cm above the cardia. Each child or relative is instructed to record any symptoms, time and position of the body (supine position, standing) and at the same time to press the button on the device [11][12][13][14]. The test is positive if the pH decreased below four for more than five seconds [17].…”
Section: Methodsmentioning
confidence: 99%
“…Each patient or caregiver was trained to record in a table any symptoms occurred, the time and body position (supine, standing) and, at the same time, using the button provided on the device. [12][13][14] All patients with positive score received treatment with proton pump inhibitors and they were evaluated again after 2 months. Statistical Package for Social Sciences software 20 was used for the statistical data processing.…”
Section: Inclusion Criteriamentioning
confidence: 99%